Substituted 2-(2-aminopyrimidin-4-yl)pyridine-4-carboxylates as potent inhibitors of JumonjiC domain-containing histone demethylases. (September 2016) - Roatsch, Martin; Robaa, Dina; Pippel, Martin; Nettleship, Joanne E; Reddivari, Yamini; Bird, Louise E; Hoffmann, Inga; Franz, Henriette; Owens, Raymond J; Schüle, Roland; Flaig, Ralf; Sippl, Wolfgang; et al.
Background: Aberrant expression of iron(II)- and 2-oxoglutarate-dependent JumonjiC histone demethylases has been linked to cancer. Potent demethylase inhibitors are drug candidates and biochemical tools to elucidate the functional impact of demethylase inhibition.Methods & results: Virtual screening identified a novel lead scaffold against JMJD2A with low-micromolar potency in vitro . Analogs were acquired from commercial sources respectively synthesized in feedback with biological testing. Optimized compounds were transformed into cell-permeable prodrugs. A cocrystal x-ray structure revealed the mode of binding of these compounds as competitive to 2-oxoglutarate and confirmed kinetic experiments. Selectivity studies revealed a preference for JMJD2A and JARID1A over JMJD3.Conclusion: Virtual screening and rational structural optimization led to a novel scaffold for highly potent and selective JMJD2A inhibitors.